Developing an Inclusive Learning Framework through Artificial Intelligence and Multicultural Education in Brazil - L.M. Carvalho (Journal of Cultural Relativism (JCR), 2025)
The rapid advancement of artificial intelligence (AI) has transformed educational systems worldwide, creating new opportunities for personalized learning, accessibility, and educational inclusion. Simultaneously, increasing cultural diversity requires educational institutions to adopt multicultural approaches that promote equity, intercultural understanding, and social inclusion. This study explores the integration of artificial intelligence and multicultural education in developing an inclusive learning framework for Brazil, a country characterized by significant cultural, ethnic, and linguistic diversity. Using a qualitative systematic literature review approach, the study synthesizes contemporary research on AI in education, multicultural education, inclusive learning, and cultural diversity. The findings indicate that AI technologies can enhance inclusive learning through personalized instruction, adaptive assessment, language support, and equitable access to educational resources. When combined with multicultural educational principles, AI can facilitate culturally responsive learning experiences that recognize and respect diverse student backgrounds. However, challenges related to algorithmic bias, digital inequality, and ethical concerns must be addressed to ensure equitable implementation. The study proposes an inclusive learning framework that integrates technological innovation with multicultural educational values to support educational equity and social inclusion in Brazil.